2014
DOI: 10.1002/qua.24612
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Brønsted acid–noble atom contacts: A reevaluation of hydrogen bonding criteria

Abstract: Xenon atoms interact weakly and reversibly with different molecular systems and human body. In this report, we consider their participation in hydrogen bonding in relation to analogous interactions of Ne, Ar, and Kr. Acid-noble atom dimers, AAHÁÁÁRg, are examined by the quantum theory of atoms in molecules and the results are discussed using several independent parameters. Different factors of this complexation are recognized: (i) the AH acidity and the Rg basicity, (ii) the AH structure, (iii) the electronega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…69,70 Recent studies on isolated, H-bonded-like Xe•••HA dimers (where AH are different acids: NCH, CNH, ClH, BrH, ClOH, BrOH, CHCOOH, CFCOOH, and CClCOOH) revealed very big δ( 129 Xe) sensitivity to AH acidity. 69 Calculated energy formation of the A−H•••Xe dimers and the 129 Xe deshielding, resulting from these contacts, are within 1.4−5.4 kJ/mol and 54−85 ppm, respectively. 69 For each Xe•••HA dimer, the shielding tensor principal component σ zz represents the highest shielding direction (z) parallel or almost parallel to the Xe•••H direction.…”
Section: Resultsmentioning
confidence: 99%
“…69,70 Recent studies on isolated, H-bonded-like Xe•••HA dimers (where AH are different acids: NCH, CNH, ClH, BrH, ClOH, BrOH, CHCOOH, CFCOOH, and CClCOOH) revealed very big δ( 129 Xe) sensitivity to AH acidity. 69 Calculated energy formation of the A−H•••Xe dimers and the 129 Xe deshielding, resulting from these contacts, are within 1.4−5.4 kJ/mol and 54−85 ppm, respectively. 69 For each Xe•••HA dimer, the shielding tensor principal component σ zz represents the highest shielding direction (z) parallel or almost parallel to the Xe•••H direction.…”
Section: Resultsmentioning
confidence: 99%
“…1. 35 Thus it can be concluded that the mutual interconnection between both theoretical r(r c ) and experimental DA 1/2 This journal is © The Royal Society of Chemistry 2014 parameters does exist. It is also clear from the Fig.…”
mentioning
confidence: 97%
“…The Ng–HF (Ng = Ne, Ar, Kr, Xe) species were recently investigated within a general study on the formation of hydrogen bonding by Ng atoms. , Thus, while Kr–HF and Xe–HF were predicted to be stable and to feature properties typical of H-bonding contacts, Ne–HF and Ar–HF were even unstable when basis set superposition error and zero-point vibrational energy corrections were included. Interestingly, the study of the H mol ( r ) function actually confirms the different bonding situations of the lightest and the heaviest Ng–HF.…”
Section: Resultsmentioning
confidence: 99%
“…21 Following pioneering applications reported so far, 22-25 the AIM theory is extensively employed to analyze the bonding situation of noble-gas compounds. [26][27][28][29][30][31] In general, within the AIM theory, one explores the topology ρ(r) is relatively large and ∇ 2 ρ(r) < 0, while for typical non-covalent (closed-shell) interactions such as ionic bonds, hydrogen bonds, and van der Waals contacts, at the BCP ρ(r) is relatively small, and ∇ 2 ρ(r) > 0. 21 These criteria, however, must often contend with conflicting indications from independent evidence, and further analysis is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation